Unlocking the Potential of Biomass Energy in Pakistan - Saghir, Muhammad; Zafar, Shagufta; Tahir, Amiza; Ouadi, Miloud; Siddique, Beenish; Hornung, Andreas (Frontiers in Energy Research, 2019)
Being a developing economy, Pakistan is facing a severe energy crisis that limits its economic development. Pakistan relies heavily on energy resources like natural gas, oil, hydropower, nuclear, coal and liquefied petroleum gas (LPG) which contribute to primary energy supplies as 48.3%, 32.1%, 11.3%, 7.6%, and 0.6% respectively. Because of the rapidly growing population and economy, Pakistan’s energy needs are huge; to accomplish these energy necessities, Pakistan is continually spending $7-9 billion on the import of fossil fuels. To resolve the serious issues of energy availability, Alternative Energy Development Board (AEDB) of Pakistan is currently exploring the development of renewable energy technologies in Pakistan that will be beneficial for the developing economy such as Pakistan to minimize the growing energy crisis. Out of all the renewable energy resources, biomass is considered the best and easily accessible source of energy with its unique environment-friendly nature, constant, wider availability and ease of integration into existing infrastructure. Despite the presence of an abundance of biomass energy resource, there is still a need for excellent work on the use of these sources to produce energy. This literature review explores the availability of biomass resource in Pakistan and its potential for addressing rapidly growing energy demand in the country that can assist in the stabilization of a country’s energy demand for challenged economic development. Furthermore, while producing energy a vast range of added value products can also be produced from biomass for use in domestic market and for export thus truly contributing to sustainable economic development of Pakistan.